PENERAPAN PRINSIP KEADILAN PANCASILA DALAM PERDA NOMOR 8 TAHUN 2009 TENTANG PENDIRIAN LPPL ATV KOTA BATU - Ellen Meianzi Yasak (Universitas Tribhuwana Tunggadewi, 2014)
Batu City is the Administrative City (Kotatif) recently founded in 2001. As the city who were aged 13 years, many things that must be addressed, for instance formulation of the region policies. Regional Regulation (Perda) of the Local Public Broadcasting (LPPL) ATV, becomes the object of study in this research. Because as a product policy, Perda ATV assessed not in accordance with the above policy consideration. This analysis measured how much regulation applied the principle of justice. The results showed, content of Perda still very broad and have not touched the realm of justice or aspired empowerment as in law.